Preliminary research on the environment and the hydrobiological characteristics of freshwater bodies in Phong Nha cave area, Quang Binh province - Hai, Ho Thanh; Thanh, Danh Ngoc; Son, Nguyen Kiem; Mach, Phan Van; Anh, Le Hung; Do, Nguyen Khac; Cuong, Duong Ngoc (Academia Journal of Biology, 2015)
In order to more understand on characteristics of the water environment and hydrobiological condiction of the freshwater bodies in the Phongnha cave area, a survey was carried out in June, 2001. Preliminary research results show that the water quality of the waterbodies in the Phongnha cave are not polluted. In general, there is no difference on hydro-chemical features between the river sections inside and outside of the Phongnha cave. The CN concentration of the river in dry season is many time lower than in rainy season. 54 phytoplankton species, 39 zooplankton species, 14 mollusc and benthic crustacean species, 13 taxa of insectine family and 36 fish species are recorded. Some species of the brackish waters found here indicated that the river in the Phong Nha cave is still impacted by the riverine mouth areas. The hydrobiological fauna of the river section inside the Phong Nha cave is poor in species composition in comparison to that outside the cave. Two new crustacean species of Diaptomidae are found here (one new genus). For this reason, it shows that the characteristics of the aquatic community in the waters inside of the cave are little known. It is necessary to establish a project for more comprehensive study on the water environment and the hydrobiogical fauna of the waters inside of karst caves, of which the Phongnha cave should be a case to study.